KEBERTAHANAN KOSAKATA ANATOMI TUBUH MANUSIA DALAM BAHASA MUNA PADA PENUTUR BAHASA MUNA - Wa Ode Halfian; Fina Amalia Masri; Zahrani Zahrani; Ali Mustopa (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
Regional languages are one of the sources of Indonesian language development, therefore the existence of regional languages is very necessary to be maintained or preserved. Muna language is one of the regional languages in Southeast Sulawesi. The current position of the Muna Regional language has gone down. The condition of the local language-speaking community who is reluctant to use the local language and changes in the environment in which they live are one of the contributing factors. The purpose of this study was to describe the percentage level of survival of the vocabulary of the anatomy of the human body in the Muna language among Muna speakers at BTN Kendari Permai, Kendari City. This study used the theory of language survival, vocabulary, and ecolinguistics theory. The methods used in this research were qualitative and quantitative methods. The results of data analysis showed that the anatomical vocabulary of the human body in Muna language for Muna speakers at BTN Kendari Permai were still survives well. From the 40 respondents who filled out the questionnaire, 81% of the respondents still knew, understood and explained the names of their anatomy well. From the 60 vocabularies proposed in the questionnaire, 87% (52) of vocabulary still survive and 13% (8) of vocabularies have not survived.